2019
DOI: 10.1159/000496620
|View full text |Cite
|
Sign up to set email alerts
|

Fabry Disease Prevalence in Renal Replacement Therapy in Turkey

Abstract: Background: Fabry disease (FD) is an X-linked lysosomal storage disorder resulting from lack of alpha-galactosidase A (AGALA) activity in lysosomes. Objective: In this multicenter study, we aimed to evaluate the prevalence of FD in renal transplant (Tx) recipients in Turkey. We also screened dialysis patients as a control group. Methods: All Tx and dialysis patients were screened regardless of the presence of a primary disease. We measured the AGALA activity in all male patients as initial analysis. Mutation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…Each large-scale screening study with >5000 subjects [51][52][53] found >10 GLA variants. In these studies, the most common variants were p.L415P (classical), p.R363H (late-onset), p.M296I, and p.R112H and found in Argentina [51,68].…”
Section: High-risk Screening For Fd In Individuals With Renal Manifestationsmentioning
confidence: 99%
“…Each large-scale screening study with >5000 subjects [51][52][53] found >10 GLA variants. In these studies, the most common variants were p.L415P (classical), p.R363H (late-onset), p.M296I, and p.R112H and found in Argentina [51,68].…”
Section: High-risk Screening For Fd In Individuals With Renal Manifestationsmentioning
confidence: 99%
“…The mean endogamy ratio in Turkey is 23.2% regarding the data published in 2017 by the Turkish Statistical Institute [14]. 43 from 71 family members were affected in the study of Yalin et al [15]. Therefore, we tried to screen family members of index cases as much as we can.…”
Section: сLinical Case Reportsmentioning
confidence: 99%
“…Numerous studies have examined the prevalence of Fabry disease in haemodialysis (HD) populations worldwide, with estimated prevalence ranging from 0.12% [28,29] to 0.36% [30]. Fabry screening studies of Japanese HD populations [17,[31][32][33][34][35] estimate prevalence at 0.3 to 0.7% [32,34,35].…”
Section: Introductionmentioning
confidence: 99%
“…A Brazilian study estimated the prevalence of Fabry disease in haemodialysis patients to be 0.12% [28]. A recent Turkish study identified 17 cases of FD in male patients on renal replacement therapy (RRT), with 15 of those cases in patients who have had renal transplants (0.39%, n = 3882), two cases identified in patients on dialysis (0.12%, n = 1655), and an overall prevalence rate of 0.31% [29]. A systematic review of Fabry screening studies in high-risk populations revealed 12 studies of dialysis populations [39].…”
Section: Introductionmentioning
confidence: 99%